TOWARDS THE DREAM (OR BACKWARDS) ON ALEXEY FEDORCHENKO’S FILM «FIRST ON THE MOON» (Филологический класс, 2018)
The genre of documentary mystification (mockumentary) is investigated in the article with use of one of its first versions in the Russian film history — Alexey Fedorchenko’s film “First on the Moon” (2005). The film is considered through the lens of the typology of the attitudes towards the Soviet civilizational project that existed in 2000s. The analysis is centered around the problem of trust, first, towards the Soviet project, second, towards the motives of its proponents, third, towards the ways in which this project was represented and popularized. The article aims to link the history of the Soviet project with the ways it was represented in the documents, documentary film, the testimonies, artistic representations and propaganda. The method of comparison is applied to the strategies of Soviet industrialization (mobilization), the socialist manufacturing (embezzlement-oriented type of economy) and the socialist reporting (statistics falsification, achievements demonstration, erasure of the opposition between a fact and an artistic image). The role of the secret services and the secrecybased regime in the problem of trust towards the information about the past is considered. The question about the place of the genre of documentary mystification in the postmodern paradigm is raised and the conclusion is drawn that the aesthetic position of the film director is marked by an abandonment of conceptualism and refusal to maintain the ironic distance towards the Soviet past.